First-principles study of transition metal (Ti, Nb)-doped NaAlH4. (9th February 2016) - Yu, Suye; Ju, Xin; Wan, Chubin; Li, Shina
Abstract: First-principles calculations were carried out to clarify the effect of Ti and Nb dopants on the structure, energetics, and electronic properties of NaAlH4 in bulk and surface. Our calculations revealed that Ti preferred to substitute for the AlH site of AlH4 unit, whereas Nb preferred to substitute for the Al atom in bulk. Structural analysis showed that the structure of Nb-doped NaAlH4 bulk was looser than Ti-doped NaAlH4 bulk. The analysis of density of states illustrated that Ti interacted with Al atoms in covalent bonds, whereas Nb interacted with Al atoms mainly in weak ionic bonds in Ti- and Nb-doped NaAlH4 bulk. Thus, the diffusion of hydrogen atoms and AlHx units was more favorable in Nb-doped bulk than in Ti-doped bulk. The location of Nb atom in the NaAlH4 (001) surface was investigated, and an active NbAl2 H10 –Al2 H6 complex was observed. The results of hydrogen removal energies of the complex indicated that the removal of H atoms, especially the H atoms in the Al2 H6 unit, was much simpler than in pure NaAlH4 . Highlights: The roles of H vacancies on the dehydrogenation of NaAlH4 bulk were discussed. Nb-doped was better than Ti-doped NaAlH4 bulk on the kinetics of dehydrogenation. An active NbAl2 H10 –Al2 H6 cluster formed in the Nb-doped NaAlH4 (001) surface. Nb dopant favored the dehydrogenation of NaAlH4 by forming Nb–H and Nb–Al phases. Nb dopant produced an extensive effect stronger than that of Ti dopant.